Working Time as an Investment? The Effects of Unpaid Overtime on Wages, Promotions, and Layoffs - Silke Anger (Deutsches Institut für Wirtschaftsforschung (DIW), 2005)
Whereas the number of paid overtime hours declined over the last two decades in Germany, a different trend can be observed for unpaid overtime. We analyze future consequences of unpaid work with respect to a worker?s career advancement, such as higher future wages and probabilities of promotion or job retention, which might help to explain why an increasing fraction of employees are working extra hours for free. Data from the SOEP for the years 1993 to 2004 are used to examine whether working a higher number of unpaid extra hours involves a higher probability of promotion and excess earnings growth, and a lower probability of layoff in subsequent years. The pooled, random effects, and fixed effects logit estimates reveal limited evidence for the investment character of unpaid overtime hours with respect to future wage growth and promotions. Moreover, unpaid extra hours do not help to prevent future layoffs, except for East German women. For West German men, unpaid overtime hours are positively associated with the risk of future dismissal.
Keywords: J33; J22; J41; 330; Unpaid overtime; promotion; wage growth; layoff; labor supply